Mapping the Potential of e-Micromobility Vehicles for Sustainable Urban Development – the Case of Gyor, Hungary - Petra Szakonyi (Chemical Engineering Transactions)
Can the advancement of electromobility (e-mobility) be the key to achieving sustainable development and transportation in urban areas? While electric vehicles typically produce less environmental impact compared to conventional cars—such as reduced noise and air pollution—they still generate various externalities, including congestion costs, accidents, and adverse effects on landscapes and public spaces. In contrast, light e-micro mobility vehicles, particularly e-scooters, have emerged as a new transportation alternative in many cities worldwide and appear to facilitate a shift towards more sustainable modes of transport due to their advantages. However, e-micromobility can only contribute to sustainable urban development if careful planning and development are implemented. This study explores the history, current status, and future potential of e-micro mobility advancements. As part of the primary research, we assessed the socio-economic profiles and usage behaviors of e-micro mobility users in Gyor, Hungary. We also examined the share of e-micro mobility users in the modal split, their travel patterns, and their needs and desires. The findings indicated that e-micro mobility vehicles primarily substitute walking and public transport, with fewer trips being made by private cars. Ultimately, the study concluded that a shift from car usage to e-micro mobility is achievable, provided there are suitable policy frameworks and sustainable urban and transportation development strategies in place.